Effects of methanol to diesel ratio and diesel injection timing on combustion, performance and emissions of a methanol port premixed diesel engine. (15th January 2016) - Wei, Lijiang; Yao, Chunde; Han, Guopeng; Pan, Wang
Abstract: In this study, port premixed methanol compression ignition combustion was performed on a heavy-duty diesel engine. The effects of methanol to diesel ratio (RMD ) and DIT (diesel injection timing) on combustion, performance and emissions were comprehensively investigated. The experimental results demonstrated that RMD and DIT played important roles in combustion and emission control. With the increasing RMD, the ignition delay was prolonged and the combustion duration was shortened. And as DIT retarded, the ignition delay was also prolonged and the combustion duration basically remained unchanged at the beginning, and then followed by a slight decrease. The maximum in-cylinder mean temperature decreased with the retarding DIT and it was largely affected by the combine of RMD and DIT. The brake thermal efficiency remained stable at low RMD, but showed a slight decrease at high RMD. NOX and soot emissions and the RI (ringing intensity) were all decreased as RMD increase, while HC and CO emissions increased significantly. With the retarding DIT, HC emission firstly increased and then decreased, while CO emission always increased. It was more important that the trade-off relationship between NOX and soot was significantly improved with the increasing RMD and almost disappeared at RMD 1.54. Highlights: Impacts of RMD and DIT on engine performance were investigated. Ignition delay was prolonged with the increasing RMD and the retarding DIT. NOX, soot emission and ringing intensity were decreased with the increase of RMD. The trade-off relationship between NOX and soot almost disappeared at RMD 1.54.